2010
DOI: 10.1007/s10753-010-9230-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin Synthase-1 mRNA Expression Does Not Correlate with Endogenous Cardiolipin Synthase Enzyme Activity In Vitro and In Vivo in Mammalian Lipopolysaccharide Models of Inflammation

Abstract: We examined if lipopolysaccharide (LPS) treatment of mice affected cardiolipin (CL) synthesis. Mice were injected i.p. with LPS, the liver harvested, and CL synthase (CLS) enzyme activity and its mRNA expression examined. Treatment of mice with LPS resulted in a 55% decrease (p < 0.01) in mRNA expression of murine CLS compared to controls, but CLS enzyme activity was unaltered. The pool size of liver CL and other phospholipids were unaltered by LPS treatment. A similar effect was observed in murine epidermal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…The protein turnover rate of mammalian CLS is slow (Lu et al . ). This might account for the modest 37% reduction in CL mass observed in hCMEC/D3 cells with knock down of CLS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The protein turnover rate of mammalian CLS is slow (Lu et al . ). This might account for the modest 37% reduction in CL mass observed in hCMEC/D3 cells with knock down of CLS.…”
Section: Discussionmentioning
confidence: 97%
“…RNAi-mediated knockdown of CLS in both human and other mammalian cells was previously reported to partially reduce CL levels (Choi et al 2007;Ji et al 2012;Chu et al 2013). The protein turnover rate of mammalian CLS is slow (Lu et al 2011). This might account for the modest 37% reduction in CL mass observed in hCMEC/D3 cells with knock down of CLS.…”
Section: Discussionmentioning
confidence: 98%
“…There appears to be tight coordination between translation and transcription of CLS in yeast (Su and Dowhan, 2006). Further, thyroxine has been shown to increase hepatic enzyme activity (Hostetler, 1991) and lipopolysaccharide decreases CLS mRNA levels in the liver (Lu et al, 2011). CLS1 normally resides within the inner membrane of mitochondria (Chen et al, 2006), where it could potentially colocalize with a pool of PINK1 (Meissner et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The observed decrease in CLS activity could be a compensatory mechanism to counteract the increased CL formed in liver of PCC rats. We previously showed that CLS mRNA expression does not correlate with endogenous CLS enzyme activity [33]. In Micrococcus lysodeikticus the end-product of CL synthesis, CL, was shown to inhibit CLS at several concentrations [34].…”
Section: Discussionmentioning
confidence: 99%